Ninth Five Year Plan 1997-2002 and Annual Plan—1997-98 Draft Proposals Volume II Part-VII Transport - Planning Commission (Planning Commission, 1997)
In the hilly State of Meghalaya, the only means of communication is road transport as such utmost importance is given for speedy development of this essential infrastructure. Meghalaya started to develop its road network from a meagre 12.35 Km/ 100 Sq. K. M., which was inherited from Assam in 1970. But at the end of Seventh Plan period it achieved a road density of 24.90 Km/100 Sq. K. M. the road density achieved upto March ‘96 is 29.30 Km/100 Sq K. M with a totals road length of 6572 K. M. out of which 2094 K. M. is surfaced. At the end of Eighth Plan the road density would go upto 29.90 Km/100 Sq. Km. The total road length would increased to 6707 Kms and the total length of surface road would be 2994 Kms. Approach to the Ninth Five year Plan;—As per recommendation of the working group set up by the Planning Commission all States in Hilly areas should achieve a road density of 40Km/100 Sq. K. M. by the year 2600 A. D. In this respect Meghalaya is lagging behind in reaching the recommended target. With the proposed outlay for Ninth Plan the road density will reach 33,693 Km/100 Sq. K, M.
Roads and Bridges Road Transport Other Transport Services Tourism Planning Department